Analysis of Polyvinylidene Fluoride Membranes Fabricated for Membrane Distillation - Minchul Ahn; Hyeongrak Cho; Yongjun Choi; Seockheon Lee; Sangho Lee (Membranes, 2021)
The optimization of the properties for MD membranes is challenging due to the trade-off between water productivity and wetting tendency. Herein, this study presents a novel methodology to examine the properties of MD membranes. Seven polyvinylidene fluoride (PVDF) membranes were synthesized under different conditions by the phase inversion method and characterized to measure flux, rejection, contact angle (CA), liquid entry pressure (LEP), and pore sizes. Then, water vapor permeability (Bw), salt leakage ratio (Lw), and fiber radius (Rf) were calculated for the in-depth analysis. Results showed that the water vapor permeability and salt leakage ratio of the prepared membranes ranged from 7.76 × 10−8 s/m to 20.19 × 10−8 s/m and from 0.0020 to 0.0151, respectively. The Rf calculated using the Purcell model was in the range from 0.598 μm to 1.690 μm. Since the Rf was relatively small, the prepared membranes can have high LEP (more than 1.13 bar) even at low CA (less than 90.8°). The trade-off relations between the water vapor permeability and the other properties could be confirmed from the results of the prepared membranes. Based on these results, the properties of an efficient MD membrane were suggested as a guideline for the membrane development.